Nintedanib-loaded anti-adhesion membrane as well as preparation method and application thereof

Through electrospinning technology, nidanib is combined with degradable polymer carrier to prepare anti-adhesion film and hydrogel with excellent mechanical properties, which solves the problem of poor adhesion prevention after surgery in the prior art, and realizes the Efficient, safe and economical adhesion prevention effects.

CN119318741APending Publication Date: 2025-01-17SOUTH CHINA UNIV OF TECH +1
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411432005.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The prior art cannot effectively prevent the occurrence of adhesions after surgery, especially in laparoscopic surgery, existing anti-adhesion products cannot completely eliminate adhesions, and there are problems of low bioavailability, side effects and high costs.

Method used

Electrospinning technology is used to combine nidanib with degradable polymer carrier to prepare anti-adhesion film and hydrogels loaded with nidanib. Hexafluoroisopropanol is used as solvent and electrospinning and ultrasonic extrusion is performed. The method of producing anti-adhesion materials with excellent mechanical properties is prepared to achieve sustained release and local release of the drug.

Benefits of technology

It significantly reduces the probability and degree of adhesion, improves the anti-adhesion effect, reduces the dosage of drugs, reduces toxic side effects, and provides a cost-effective solution suitable for different types of surgery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119318741A_ABST
    Figure CN119318741A_ABST
Patent Text Reader

Abstract

The invention discloses an anti-adhesion membrane loaded with nintedanib and a preparation method of the anti-adhesion membrane loaded with the nintedanib. The anti-adhesion membrane loaded with the nintedanib is prepared from a drug-loading substrate material and the nintedanib through electrostatic spinning, the material of the drug-loading substrate is one or more of polylactic acid, poly (p-dioxanone), a polylactic acid-glycolic acid copolymer, polycaprolactone and polyethylene glycol; a solvent adopted in the electrostatic spinning is hexafluoroisopropanol, and the voltage adopted in the electrostatic spinning is 10-14 kV. The nintedanib-loaded anti-adhesion membrane has the advantages that the tensile strength and the elongation at break are obviously improved, the mechanical property is obviously improved, the fiber distribution is uniform, the obvious anti-adhesion effect is realized, the nintedanib-loaded anti-adhesion membrane is suitable for common laparotomy, and the application prospect is wide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of medical technology, and more specifically, the present invention relates to an anti-adhesion film loaded with nintedanib and a preparation method and application thereof. Background Art

[0002] Postoperative adhesion refers to the adhesion between the postoperative wound and adjacent tissues or organs, which can lead to serious complications, including intestinal obstruction, infertility, abdominal pain and pelvic pain. Postoperative adhesion is a common problem in clinical practice. In general abdominal surgery, the incidence of adhesion is as high as 63% to 97%. Postoperative adhesion not only seriously endangers the patient's health, but also brings a huge economic burden and increases the pressure on the medical department.

[0003] At present, the prevention methods for postoperative adhesion mainly include: 1. Improving surgical methods, upgrading surgical methods, reducing the wound area, and reducing the duration of surgery. 2. Filling a layer of absorbable physical barrier between the wound and adjacent tissues or organs to block the connection between the wound and adjacent tissues. 3. Oral anti-inflammatory or pro-fibrinolytic drugs to inhibit the occurrence of adhesions by reducing the levels of cytokines related to adhesions. However, the current clinical methods for coping with adhesions have limited efficacy and cannot completely overcome the occurrence of adhesions. Therefore, more effective methods for preventing adhesions are urgently needed.

[0004] The mechanism of adhesion formation after surgery is relatively complex. The process of adhesion is usually divided into three stages: the first stage is inflammation and cell migration. When the peritoneum is injured by surgery, mesothelial cells release a variety of cytokines and chemokines to induce the initial inflammatory response. Matrix mast cells are activated to release histamine and kinin, increasing vascular permeability. Subsequently, immune cells are recruited to the injured site to release more inflammatory factors. The next stage is coagulation, fibrin deposition, and extracellular matrix reconstruction. Coagulation occurs immediately after the onset of inflammation, and plasma rich in fibrinogen infiltrates into the abdominal cavity in large quantities due to increased vascular permeability caused by the inflammatory response. At the same time, due to capillary damage caused by surgery, the coagulation mechanism in the body is activated, and prothrombin is converted into active thrombin. Under the catalysis of thrombin, fibrinogen is cleaved into fibrin and deposited at the injured site, and the extracellular matrix is ​​reestablished. The last stage is tissue reconstruction. At this stage, the damaged tissue begins to repair and rebuild and connect to the surrounding normal tissue. Adhesion tissue generally contains fat cells, smooth muscle cells and nerve fibers, and usually forms some new blood vessels to provide nutrition for these cells. In the process of adhesion, inflammatory factors such as transforming growth factor-β1 (TGF-β1) play an important role. It can accelerate fibrosis and promote the repair of blood vessels and lymphatic vessels. Therefore, downregulating the expression level of TGF-β1 can effectively prevent the occurrence of adhesion.

[0005] According to the above adhesion formation process, there are currently three main methods for adhesion prevention in clinical practice: surgery, anti-adhesion drugs, and anti-adhesion polymer barriers. During the operation, doctors should follow the following basic principles: try to avoid damaging irrelevant tissues, prevent tissue drying, carefully stop bleeding, avoid foreign body contamination, continue to flush, and carefully suture to close the wound. For patients with adhesions, adhesion lysis is required to remove the adhesions. However, it is reported that the incidence of recurrent adhesions is still very high. The method of preventing adhesions through surgery usually requires doctors to have rich clinical experience and perform high-level operations, and secondary operations will increase medical costs and cause unnecessary harm to patients.

[0006] Anti-adhesion polymer materials have always been a hot topic in adhesion-related research. So far, a variety of polymers have been approved for the treatment of postoperative adhesions at home and abroad, including polylactic acid (PLA), hydroxymethyl cellulose (CMC), sodium hyaluronate (SH), etc. Based on these polymers, a variety of anti-adhesion products are currently on the market at home and abroad. According to the differences in morphology, the commercially available anti-adhesion products can be divided into the following categories: thin films ( etc.), hydrogel ( etc.), solution ( etc.), spray ( In general, an ideal anti-adhesion product should be biodegradable and not require secondary surgery to remove; be easy to adhere to the wound and not easy to shift; provide long-term and effective protection until the wound is completely healed; not cause any inflammatory response; not cause the wound to heal more slowly; have no other side effects and be cost-effective. However, the polymer-based anti-adhesion products currently on the market often do not have all these characteristics (e.g. The texture is brittle, the strength is low, it is inconvenient to use, and it will break if you use a little force when taking it. It may not completely cover the wound, and it is expensive). Therefore, it is difficult to completely prevent the occurrence of adhesion.

[0007] Drugs to prevent adhesion are also a commonly used method to prevent adhesion in clinical practice. It is not difficult to see from the above-mentioned adhesion mechanism that inflammatory response and fibrin deposition are two key processes in the adhesion process. Currently, drugs for preventing adhesion also mainly act on these two stages. According to the different pathways of action, anti-adhesion drugs are mainly divided into three categories: anti-inflammatory drugs (corticosteroids, pentoxifylline, etc.), anticoagulants (heparin, adenosine, etc.) and pro-fibrinolytic drugs (streptokinase, urokinase, etc.). Since inflammation and coagulation reactions are also part of normal wound healing, the use of these drugs may lead to slow wound healing or even continuous bleeding, bringing new safety concerns.

[0008] In addition, considering the diversity of modern surgical methods, the treatment methods for adhesions should also be different for different surgical methods. Laparoscopic surgery is a new minimally invasive surgical method developed in recent decades; the general operation steps are as follows: first, make several small incisions with a diameter of 5 to 12 mm in different parts of the abdomen, and use a pneumoperitoneum needle to establish pneumoperitoneum (pressure 10 to 12 mmHg); then insert a laparoscope lens of a certain size into the abdominal cavity, and use the built-in high-definition camera to display the situation in the abdominal cavity in real time on a dedicated monitor. The doctor then obtains information through the monitor and uses the corresponding laparoscopic instruments to perform various surgical operations. Laparoscopic surgery has the following advantages: ① The surgical scope is small, which greatly reduces bleeding and the formation of cellulose clots. Compared with traditional open surgery, the abdominal wall wound formed by laparoscopic surgery is small, so the probability of adhesion to the organs is greatly reduced, and the adhesions formed are often relatively mild and limited. ② The operation is simple, without the need to use a tractor, fill the intestinal tube, and open and close the abdomen, which greatly reduces the risk of infection. ③ The damage to the patient's body is small, the postoperative recovery time is short, and the adhesion rate is low. Laparoscopic surgery can reduce the probability of adhesion and reduce the severity of adhesion to a certain extent, but it still cannot completely avoid the occurrence of adhesion. Therefore, anti-adhesion methods for laparoscopic surgery are still very necessary, but there are currently few reports on related anti-adhesion products for laparoscopic surgery. Considering that the opening of laparoscopic surgery is smaller, injectable hydrogels may be more suitable for adhesion prevention in laparoscopic surgery than other forms of anti-adhesion products.

[0009] Nintedanib is a new type of small molecule tyrosine kinase inhibitor that can target vascular endothelial growth factor receptors (VEGFR 1-3), platelet-derived growth factor receptors (PDGFRα, β) and fibroblast growth factor receptors (FGFR1-3), and bind to the adenosine triphosphate (ATP) binding site on the receptors, thereby blocking the process of fibrosis. Due to its excellent anti-fibrosis and anti-angiogenesis capabilities, Nintedanib has been approved by the US Food and Drug Administration for the treatment of idiopathic pulmonary fibrosis. In recent years, some reports have begun to appear at home and abroad, expanding the new use of Nintedanib and using it for the prevention and treatment of postoperative adhesions.

[0010] A large number of clinical studies have shown that the current anti-adhesion methods cannot completely prevent the occurrence of adhesions, and postoperative adhesions are still a common problem. In fact, a single method is often not enough to provide a satisfactory anti-adhesion effect. Combining two or more anti-adhesion strategies may achieve better anti-adhesion effects. However, there are currently no reports or approvals for such anti-adhesion products at home and abroad. Summary of the invention

[0011] Based on this, the object of the present invention is to provide an anti-adhesion film / anti-adhesion hydrogel loaded with nintedanib with excellent physical properties, and a preparation method and application thereof. The anti-adhesion film / hydrogel loaded with nintedanib of the present invention has a very good anti-adhesion effect.

[0012] The technical solutions for achieving the above-mentioned invention objectives include the following.

[0013] In the first aspect of the present invention, there is provided an anti-adhesion film loaded with nintedanib, which is prepared by electrospinning a drug-loaded base material and nintedanib, wherein the drug-loaded base material is one or more of polylactic acid (PLA), polydioxanone (PPDO), polylactic acid-glycolic acid copolymer (PLGA), polycaprolactone (PCL), and polyethylene glycol (PEO); the solvent used in the electrospinning is hexafluoroisopropanol.

[0014] The second aspect of the present invention provides a method for preparing the above-mentioned anti-adhesion film loaded with nintedanib, comprising the following steps: dissolving the drug-loaded base material in hexafluoroisopropanol, adding nintedanib to completely dissolve it, obtaining a spinning solution, performing electrospinning, drying to constant weight, and ultraviolet sterilization to obtain.

[0015] The third aspect of the present invention provides an anti-adhesion hydrogel loaded with nintedanib, wherein the anti-adhesion hydrogel is prepared from a drug-loaded base material and nintedanib, and the drug-loaded base material is one or more of carboxymethyl cellulose, oxidized regenerated cellulose, hyaluronic acid, and chitosan.

[0016] In a fourth aspect of the present invention, a method for preparing the above-mentioned anti-adhesion hydrogel loaded with nintedanib is provided, comprising the following steps: dissolving the drug-loaded base material in deionized water, ultrasonicating for more than 4 hours, adding nintedanib to completely dissolve it, and then sequentially extruding it through 18G, 20G, 22G and 26G sterile needles, each for 2 to 3 times, and finally sterilizing it through a sterile filter membrane to obtain it.

[0017] The fifth aspect of the present invention provides the use of the above-mentioned anti-adhesion film loaded with nintedanib, or the anti-adhesion hydrogel loaded with nintedanib in preventing postoperative adhesion.

[0018] In the present invention, after a large number of experiments, the inventors proposed that hexafluoroisopropanol is selected as a solvent, and the anti-adhesion drug nintedanib is electrospun with a degradable and absorbable polymer carrier (especially polylactic acid). During the electrospinning process, continuous and stable fibers can be produced, the spinning membrane surface is smooth, and the needle head is free of condensation; at the same time, by controlling the electrospinning voltage at 10 to 14 kV, the tensile strength and elongation at break of the anti-adhesion membrane prepared thereby are significantly improved, the mechanical properties are significantly improved, and the fiber distribution is uniform, which has a significant anti-adhesion effect.

[0019] The anti-adhesion film loaded with nintedanib of the present invention can not only play the physical barrier role of the polymer carrier material to separate the wound from the surrounding tissue, but also release the drug molecules in situ to act directly on the wound, thereby solving the problem of low bioavailability of oral drugs, significantly reducing the dosage of the drug, and reducing toxic and side effects; in addition, as the polymer material biodegrades, the drug is slowly released in the body, having a sustained-release effect, further overcoming the disadvantage of low bioavailability of oral drugs.

[0020] The anti-adhesion membrane of the present invention is suitable for common laparotomy, and the injectable drug-loaded anti-adhesion hydrogel is suitable for laparoscopic surgery with a smaller opening, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a schematic diagram of the PLA anti-adhesion film loaded with nintedanib in Example 1 of the present invention.

[0022] Figure 2 This is a SEM morphology of the PLA anti-adhesion film loaded with nintedanib according to Example 1 of the present invention.

[0023] Figure 3 This is a SEM morphology of the SH anti-adhesion hydrogel loaded with nintedanib according to Example 3 of the present invention.

[0024] Figure 4 The breaking tensile results of the anti-adhesion membrane prepared by electrospinning at different voltages in Experimental Example 1 of the present invention are shown.

[0025] Figure 5 The surface fiber morphology of the anti-adhesion membrane prepared by using different voltages in Experimental Example 1 of the present invention; from left to right are PLA-8, PLA-12, PLA-16, membrane.

[0026] Figure 6 This is the experimental result of the inhibition of fibroblast proliferation by nintedanib in Experimental Example 2 of the present invention.

[0027] Figure 7 This is a diagram of the SD rat peritoneal ischemia model constructed in Experimental Example 3 of the present invention.

[0028] Figure 8 These are the experimental results of the peritoneal ischemia model treated with the Control group in Experimental Example 3 of the present invention.

[0029] Fig. 9 The present invention is used in test example 3 Experimental results of the peritoneal ischemia model treated with the two groups.

[0030] Fig.10The results are the experimental results of the peritoneal ischemia model treated with PLA (2% NB) in Experimental Example 3 of the present invention.

[0031] Fig.11 The results are the experimental results of the peritoneal ischemia model treated with PLA (4% NB) in Experimental Example 3 of the present invention.

[0032] Fig.12 These are the experimental results of the peritoneal ischemia model treated with SH (2 mg / mL) in Experimental Example 3 of the present invention.

[0033] Fig.13 These are the experimental results of the peritoneal ischemia model treated with SH (4 mg / mL) in Experimental Example 3 of the present invention.

[0034] Fig.14 These are the results of adhesion rate, adhesion texture and adhesion toughness score of each treatment group in Test Example 3 of the present invention.

[0035] Fig.15 These are the staining results of tissue sections sampled from each treatment group in Experimental Example 3 of the present invention.

[0036] above Figures 8 to 13 In the figure, black triangles indicate adhesion and white triangles indicate no adhesion. DETAILED DESCRIPTION

[0037] In order to facilitate the understanding of the present invention, the present invention will be described more fully below. The present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0038] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used in the present invention includes any and all combinations of one or more of the related listed items.

[0039] The experimental methods in the following examples where specific conditions are not specified are generally carried out under conventional conditions, such as those described in Green and Sambrook et al., Molecular Cloning: A Laboratory Manual, 2013, or under conditions recommended by the manufacturer. The various commonly used chemical reagents used in the examples are all commercially available products.

[0040] In some embodiments of the present invention, a nintedanib-loaded anti-adhesion film is disclosed, which is prepared by electrospinning a drug-loaded base material and nintedanib, wherein the drug-loaded base material is one or more of polylactic acid, polydioxanone, polylactic acid-co-glycolic acid, polycaprolactone, and polyethylene glycol; and the solvent used in the electrospinning is hexafluoroisopropanol.

[0041] In some of the embodiments, the viscosity average molecular weight of the polylactic acid is 12w~15w, the viscosity average molecular weight of the polydioxanone is 10w~12w, the viscosity average molecular weight of the polylactic acid-glycolic acid copolymer is 14w~18w, the viscosity average molecular weight of the polycaprolactone is 10w~16w, and the viscosity average molecular weight of the polyethylene glycol is 13w~20w.

[0042] In some embodiments, the voltage used in the electrospinning is 10-14 kV, preferably 11-13 kV.

[0043] In some embodiments, the drug loading amount of the anti-adhesion film loaded with nintedanib is 2wt% to 6wt%; preferably, the drug loading amount of the anti-adhesion film loaded with nintedanib is 3.5wt% to 4.5wt%.

[0044] In some embodiments, the drug-carrying substrate material is polylactic acid. As a common biodegradable material, polylactic acid has excellent biocompatibility, safety and degradability, and also has the characteristics of good plasticity, easy processing and molding, low cost, and large-scale availability.

[0045] In other embodiments of the present invention, a method for preparing the above-mentioned anti-adhesion film loaded with nintedanib is disclosed, comprising the following steps: dissolving the drug-loaded base material in hexafluoroisopropanol, adding nintedanib to completely dissolve it, obtaining a spinning solution, performing electrospinning, drying to constant weight, and ultraviolet sterilization to obtain the obtained film.

[0046] In some embodiments, the voltage used in the electrospinning is 10-14 kV, preferably 11-13 kV.

[0047] In some of the embodiments, the electrospinning also includes the following parameters: outflow rate is 1.2±0.2mL / min, drum speed is 200±20rpm / min, slide speed is 30±3mm / s, the distance between the needle and the drum is 15±1cm, and the spinning temperature and humidity are 35±1℃ and 40±2%.

[0048] In some of the embodiments, the mass percentage concentration of the drug-loaded base material in the spinning solution is 8-12%; and the drug loading amount of the anti-adhesion membrane is 3wt%-5wt%.

[0049] In other embodiments of the present invention, a nintedanib-loaded anti-adhesion hydrogel is disclosed, which is prepared from a drug-loaded base material and nintedanib, wherein the drug-loaded base material is one or more of carboxymethyl cellulose, oxidized regenerated cellulose, sodium hyaluronate, and chitosan.

[0050] In some of the embodiments, the viscosity average molecular weight of the carboxymethyl cellulose is 9w-20w, the viscosity average molecular weight of the oxidized regenerated cellulose is 13w-21w, the viscosity average molecular weight of the sodium hyaluronate is 20w-27w, and the viscosity average molecular weight of the chitosan is 23w-29w.

[0051] In some of the embodiments, the concentration of nintedanib in the anti-adhesion hydrogel is 2 mg / mL to 6 mg / mL.

[0052] In some of the embodiments, the concentration of nintedanib in the anti-adhesion hydrogel is 3 mg / mL to 5 mg / mL.

[0053] In some of the embodiments, the concentration of nintedanib in the anti-adhesion hydrogel is 3.5 mg / mL to 4.5 mg / mL.

[0054] In other embodiments of the present invention, a method for preparing the above-mentioned anti-adhesion hydrogel loaded with nintedanib is disclosed, comprising the following steps: dissolving the drug-loaded base material in deionized water, ultrasonicating for more than 4 hours, adding nintedanib to completely dissolve it, and sequentially squeezing it through sterile needles of different specifications for 2 to 3 times, and sterilizing it through a 0.22 μm sterile filter membrane to obtain the obtained hydrogel; the sterile needles of different specifications include 18G, 20G, 22G and 26G sterile needles.

[0055] In some embodiments, the ultrasound duration is 4 to 8 hours.

[0056] In some embodiments, the concentration of the drug-loaded base material is 25 mg / mL to 35 mg / mL.

[0057] In other embodiments of the present invention, the use of the above-mentioned anti-adhesion film loaded with nintedanib or the anti-adhesion hydrogel loaded with nintedanib in preventing postoperative adhesion is disclosed.

[0058] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0059] Example 1 Anti-adhesion film loaded with 2% nintedanib and preparation method thereof

[0060] The following steps are involved:

[0061] 1. Accurately weigh 1.025g of PLA, add hexafluoroisopropanol to it to make it 10.25g, and ultrasonicate for 8h to make it completely dissolved to prepare a PLA spinning solution with a mass fraction of 10%;

[0062] 2. Further weigh 20.5 mg of nintedanib, add it to the PLA spinning solution, and shake it repeatedly to completely dissolve nintedanib, thereby obtaining a PLA spinning solution loaded with 2% nintedanib.

[0063] 3. Place a layer of release paper on the surface of the collector, connect the collector to the negative electrode, add the spinning solution into a 10ml spinning syringe, the needle specification is 20G, shake and push out the bubbles in the pipeline, and connect the needle to the positive electrode of the spinning machine; the speed of the collector is set to 200rpm / min, the flow rate of the micro pump is 1.2mL / min, the slide displacement is 100mm, the cleaning time interval is 30min, the positive voltage is 10kV, the negative voltage is -2kV, the temperature is 35℃, the humidity is 40%, and the injection volume is 6mL;

[0064] 4. After the injection is completed, the membrane is taken out and further dried at 35°C for 10 h until the membrane weight reaches a constant weight, cut and sterilize under UV to obtain a PLA anti-adhesion membrane loaded with 2% nintedanib.

[0065] The schematic diagram of the PLA anti-adhesion film loaded with nintedanib in this embodiment is as follows Figure 1 As shown, the SEM morphology is Figure 2 shown.

[0066] Example 2 Anti-adhesion film loaded with 4% nintedanib and preparation method thereof

[0067] The following steps are involved:

[0068] 1. Accurately weigh 1.036g of PLA, add hexafluoroisopropanol to it to make it 10.36g, and ultrasonicate for 8h to make it completely dissolved to prepare a PLA spinning solution with a mass fraction of 10%;

[0069] 2. Further weigh 41.4 mg of nintedanib, add it to the PLA spinning solution, and shake it repeatedly to completely dissolve nintedanib, thereby obtaining a PLA spinning solution loaded with 4% nintedanib;

[0070] 3. Place a layer of release paper on the surface of the collector, connect the collector to the negative electrode, add the spinning solution into a 10mL spinning syringe, the needle specification is 20G, shake and push out the bubbles in the pipeline, and connect the needle to the positive electrode of the spinning machine; the speed of the collector is set to 200rpm / min, the flow rate of the micro pump is 1.2mL / min, the displacement of the slide is 100mm, the cleaning time interval is 30min, the positive voltage is 14kV, the negative voltage is -2kV, the temperature is 35℃, the humidity is 40%, and the injection volume is 6mL;

[0071] 4. After the injection is completed, the membrane is taken out and further dried at 35°C for 10 hours until the membrane weight reaches a constant weight, cut and sterilize under ultraviolet light to obtain a PLA anti-adhesion membrane loaded with 4% nintedanib.

[0072] Example 3 Anti-adhesion hydrogel loaded with 2 mg / mL nintedanib and preparation method thereof

[0073] The following steps are involved:

[0074] 1. Accurately weigh 251 mg of sodium hyaluronate, add 7 ml of deionized water, and sonicate for 6 hours to completely dissolve it to prepare sodium hyaluronate hydrogel;

[0075] 2. Dissolve 16.8 mg of nintedanib in 1.4 ml of deionized water and sonicate to completely dissolve it;

[0076] 3. Add the dissolved nintedanib to the prepared sodium hyaluronate hydrogel, and then extrude the gel through 18G, 20G, 22G and 26G sterile needles in sequence, three times each. Finally, add the prepared hydrogel into a 10mL syringe and sterilize it through a 0.22μm filter membrane to obtain an anti-adhesion hydrogel loaded with 2mg / mL nintedanib.

[0077] The SEM morphology of the anti-adhesion hydrogel loaded with nintedanib in this example is as follows Figure 3 shown.

[0078] Example 4 Anti-adhesion hydrogel loaded with 4 mg / mL nintedanib and preparation method thereof

[0079] The following steps are involved:

[0080] 1. Accurately weigh 242 mg of sodium hyaluronate, add 7 mL of deionized water, and sonicate for 6 hours to completely dissolve it to prepare sodium hyaluronate hydrogel;

[0081] 2. Dissolve 32 mg of nintedanib in 1 mL of deionized water and sonicate to completely dissolve it;

[0082] 3. Add the dissolved nintedanib to the prepared sodium hyaluronate hydrogel, and then extrude it through 18G, 20G, 22G and 26G sterile needles in sequence, three times each. Finally, add the prepared hydrogel into a 10mL syringe and sterilize it through a 0.22μm filter membrane to obtain an anti-adhesion hydrogel loaded with 4mg / mL nintedanib.

[0083] Example 5 Anti-adhesion film loaded with nintedanib and preparation method thereof

[0084] The following steps are involved:

[0085] 1. Accurately weigh 1.025g PPDO, add hexafluoroisopropanol to it to make it 10.25g, and ultrasonicate for 8h to make it completely dissolved to prepare a spinning solution with a mass fraction of 10% PPDO;

[0086] 2. Further weigh 20.5 mg of nintedanib, add it to the PPDO spinning solution, and shake it repeatedly to completely dissolve nintedanib, thereby obtaining a PPDO spinning solution loaded with 2% nintedanib.

[0087] 3. Place a layer of release paper on the surface of the collector, connect the collector to the negative electrode, add the spinning solution to a 10mL spinning syringe with a 20G needle, shake and push out the bubbles in the pipeline, and connect the needle to the positive electrode of the spinning machine; set the collector speed to 200rpm / min, the micro pump flow rate to 1.2mL / min, the slide displacement to 100mm, the cleaning time interval to 30min, the positive voltage to 10kV, the negative voltage to -2kV, the temperature to 35℃, the humidity to 40%, and the injection volume to 6mL;

[0088] 4. After the injection is completed, the membrane is taken out and further dried at 35°C for 10 h until the membrane weight reaches a constant weight, and then cut and sterilized by UV to obtain a PPDO anti-adhesion membrane loaded with 2% nintedanib.

[0089] Comparative Example 1 PLA film and preparation method thereof

[0090] The following steps are involved:

[0091] 1. Accurately weigh 1.016g of PLA, add hexafluoroisopropanol to it to make it 10.16g, and ultrasonicate for 8h to make it completely dissolved to prepare a PLA spinning solution with a mass fraction of 10%;

[0092] 2. Place a layer of release paper on the surface of the collector, connect the collector to the negative electrode, add PLA spinning solution to 10mL spinning syringe, select 20G needle specification, shake and push out the bubbles in the pipeline, and connect the needle to the positive electrode of the spinning machine; the speed of the collector is set to 200rpm / min, the flow rate of the micro pump is 1.2mL / min, the slide displacement is 100mm, the positive voltage is 10kV, the negative voltage is -2kV, the temperature is 35℃, the humidity is 40%, and the injection volume is 6mL;

[0093] 3. After the injection is completed, the film is taken out and further dried at 35°C for 10 hours until the film weight reaches a constant weight, cut into small pieces of 10*10 cm and sterilized by ultraviolet light to obtain the PLA film.

[0094] Comparative Example 2 HA hydrogel and preparation method thereof

[0095] The following steps are involved:

[0096] 1. Accurately weigh 246 mg of sodium hyaluronate, add 8.2 mL of deionized water, and sonicate for 6 hours to completely dissolve it to prepare a 30 mg / mL sodium hyaluronate hydrogel;

[0097] 2. Add the prepared hydrogel into a 10 mL syringe, sterilize it through a 0.22 μm filter membrane, and set aside.

[0098] Experimental Example 1 Effects of solvent and voltage on preparation of anti-adhesion film by electrospinning

[0099] 1. Solvent

[0100] This test example compares the effects of three electrospinning solvents, N,N-dimethylformamide (DMF), chloroform and hexafluoroisopropanol, on the preparation of anti-adhesion membranes by electrospinning when the drug-carrying substrate material is polylactic acid according to the preparation method of the present invention.

[0101] According to the preparation method of Example 1, 10 wt% PLA spinning solution was prepared with DMF, chloroform and hexafluoroisopropanol respectively, spinning was carried out at a voltage of 12 kV, and the filament discharge effect at the needle head and the morphology of the spinning film were observed. The experimental results are shown in Table 1.

[0102] Table 1 Effect of solvent on electrospinning effect

[0103] Solvent Wire drawing effect Spinning membrane morphology DMF There are fibers, but they are not continuous, and there is condensation at the needle tip. The fiber membrane surface is rough with dot-like protrusions Chloroform No fiber No fiber film formation Hexafluoroisopropanol There are continuous, stable fibers and no condensation on the needle tip The surface of the spinning membrane is smooth and uniform

[0104] From the results in Table 1, it can be seen that in this drug-loaded reaction system, when chloroform is used as a solvent, no fibers are produced at the needle tip, which may be due to the fact that the chloroform volatilization rate is too fast; when DMF is used as a solvent, although fibers are produced, they are intermittent and discontinuous, which may be due to the slow volatilization of DMF, which is easy to condense at the needle tip and block-like protrusions appear on the surface of the spinning membrane. In contrast, hexafluoroisopropanol has the best spinning effect, the produced fibers are continuous and stable, the spinning membrane surface is smooth, and hexafluoroisopropanol has a low boiling point and evaporates quickly at room temperature, which is easy to remove. Therefore, hexafluoroisopropanol is selected as the spinning solvent in subsequent experiments.

[0105] 2. Voltage

[0106] In the study of preparing the anti-adhesion film of nintedanib, we found that voltage also has a great influence on the performance of the anti-adhesion film of nintedanib. A 10wt% PLA spinning solution was prepared with hexafluoroisopropanol, and spinning was performed at 8kV, 12kV and 16kV positive voltages respectively (other conditions were the same as in Example 1) to obtain anti-adhesion films, which were marked as PLA-8, PLA-12 and PLA-16 respectively. At the same time, commercially available Anti-adhesion membrane was used as control.

[0107] The four anti-adhesion films were cut into 1*5cm rectangles and subjected to breaking tensile tests on a universal material testing machine. The results are as follows: Figure 4 And as shown in Table 2.

[0108] Table 2 Effect of voltage on tensile strength of spinning membrane

[0109]

[0110] from Figure 4 As shown in Table 2, in this drug loading reaction system, as the voltage increases, the tensile strength and elongation at break of the spinning membrane gradually increase. From 8 to 12 kV, the tensile strength of the PLA spinning membrane increases by 2.36 times, and the maximum elongation at break increases by 1.85 times. The mechanical properties are significantly improved. When the voltage continues to increase to 16 kV, the improvement effect gradually decreases, the tensile strength increases by 1.19 times, and the maximum elongation at break increases by 1.07 times. At the same time, the tensile strength of the PLA membrane spun at 12 kV is higher than that of the commercially available The film thickness increased by 2.53 times, and the maximum elongation at break increased by 179.82 times.

[0111] The three PLA films and Cut into 0.5*0.5cm small pieces, spray gold, and take SEM to observe the fiber morphology on the surface of the spinning membrane. The results are as follows Figure 5 shown.

[0112] from Figure 5 It can be seen that according to the results of breaking tension and SEM, the best effect is achieved when the spinning voltage is 12kV. We analyzed the possible situation as follows: when the spinning voltage is low (8kV), the electric field force is small and it is difficult to overcome the surface tension of the spinning solution itself, which limits the stretching and splitting of the spinning solution, resulting in uneven fiber distribution. If the voltage is too high (16kV), the jet volume of the spinning solution increases and the jet speed increases, which is not conducive to the stretching and splitting of the jet, thus also causing the fiber uniformity to deteriorate. In addition, the commercially available The surface of the anti-adhesion membrane is smooth and has no fibrous structure.

[0113] In addition, the above results show that the anti-adhesion membrane prepared by the method of the present invention has good mechanical strength, uniform surface fiber distribution, high porosity, and significantly better physical properties than commercially available Anti-adhesion film.

[0114] Experimental Example 2: Experimental study on the inhibition of fibroblast proliferation by nintedanib

[0115] In this experimental example, three cell lines, 3T3 (mouse fibroblasts), BEND.3 (mouse brain microvascular endothelial cells), and MEF (mouse embryonic fibroblasts) (all purchased from the American type culture collection, ATCC) were used to verify the inhibitory effect of nintedanib (NB) on fibroblast proliferation.

[0116] First, 3T3, BEND.3, and MEF cells were inoculated on 96-well plates, respectively, and cultured at 37°C, 5% CO2, and 90% humidity for 24 hours. NB was then added for co-incubation to a final concentration of 0, 0.25, 0.5, 1, 2.5, 5, 10, and 20 mm. Three replicate wells were set for each concentration. After co-incubation for 24 hours, the cell survival rate was measured by the MTT method. The experimental results are shown in Figure 2. Figure 6 shown.

[0117] from Figure 6 The results showed that nintedanib showed significant proliferation inhibitory effects on 3T3, BEND.3 and MEF cells.

[0118] Experimental Example 3: Verification of the anti-adhesion effect using the SD rat peritoneal ischemia model

[0119] After the experimental SD rats were purchased, they were kept in the laboratory animal room for 7 days before the experiment was carried out to ensure that they adapted to the environment.

[0120] 1. Construction of peritoneal ischemia model

[0121] The experimental rats were anesthetized by intramuscular injection of 1 mL / kg of Shutai-50; after anesthesia, the rats' abdominal hair was shaved to expose the epidermis and the skin was disinfected with iodalcon disinfectant; the rats were placed supine on the operating table, and a longitudinal incision of about 4 cm was made in the lower abdomen along the midline of the abdomen; the rat peritoneum was slightly turned outward, a piece of peritoneal tissue was gently clamped with hemostatic forceps, and then the clamped tissue was knotted with surgical suture silk thread (without needle) to artificially create an ischemic nodule with a diameter of about 0.5 cm; four ischemic nodules were created on each side of the peritoneum using the same method, with a spacing of 1 cm between the nodules on the same side and 1.5 cm from the midline incision; after the ischemic knots on both sides were created, the abdominal wall incision was sutured with 4-0 surgical suture absorbable (with needle), and then the abdominal skin incision was sutured with 2-0 surgical suture silk thread (with needle); the suture site was disinfected with iodalcon disinfectant and blood was wiped off, and finally the rats were placed back in the mouse cage lying on their sides, and continued to be raised for 7 days after they woke up. The peritoneal ischemia model of SD rats was constructed as follows Figure 7 shown.

[0122] 2. Grouping

[0123] The experimental rats were divided into 8 groups, 8 in each group, and marked as Control group, The PLA group (Comparative Example 1), PLA (2% NB) group (Example 1), PLA (4% NB) group (Example 2), SH (Comparative Example 2), SH (2 mg / mL) (Example 3), and SH (4 mg / mL) (Example 4) were given different treatments.

[0124] Control group: the ischemic nodules were created according to the above standard process and then the abdomen was sutured and closed without any treatment;

[0125] Group: After the ischemic nodule was created, a 4*5 cm piece of commercially available The anti-adhesion membrane is applied to the surface of the ischemic nodules to ensure that it completely covers all nodules and blocks their contact with the abdominal organs, and then the abdomen is sutured and closed;

[0126] PLA group: After the ischemic nodules were created, a 4*5 cm piece of PLA film of Comparative Example 1 was cut and attached to the surface of the ischemic nodules to ensure that it could completely cover all the nodules;

[0127] PLA (2% NB) group: After the ischemic nodules were created, a 4*5 cm piece of drug-loaded (2% NB) PLA anti-adhesion film of Example 1 was cut and attached to the surface of the ischemic nodules to ensure that it could completely cover all the nodules;

[0128] PLA (4% NB) group: After the ischemic nodules were created, a 4*5 cm piece of drug-loaded (4% NB) PLA anti-adhesion film of Example 2 was cut and attached to the surface of the ischemic nodules to ensure that it could completely cover all the nodules;

[0129] SH group: After the ischemic nodules were created, 0.1 mL of HA hydrogel (Comparative Example 2) was uniformly injected on the surface of each nodule and spread evenly;

[0130] SH (2 mg / mL) group: After the ischemic nodules were created, 0.1 mL of the drug-loaded (2 mg / mL NB) SH anti-adhesion hydrogel of Example 3 was uniformly injected on the surface of each nodule and spread evenly;

[0131] SH (4 mg / mL) group: After the ischemic nodules were created, 0.1 mL of the drug-loaded (4 mg / mL NB) SH anti-adhesion hydrogel of Example 4 was uniformly injected on the surface of each nodule and spread evenly.

[0132] 3. Evaluation method of anti-adhesion effect

[0133] On the eighth day after the operation, the experimental rats were anesthetized again with Zota-50 and the abdomen was opened to obtain the ischemic nodule tissue and adhesion tissue of the abdominal wall of the experimental rats. Eight tissues were randomly selected from each group for hematoxylin-eosin staining:

[0134] (1) Wash thoroughly with saline, then immerse in 10% neutral formalin fixative at 4°C for 24 hours;

[0135] (2) The tissue was dehydrated in different concentrations of ethanol (70%, 80%, 90%, 95%, 100%), each time for 40 min;

[0136] (3) The tissue was immersed in three xylene solutions in sequence for 1 h each;

[0137] (4) The tissue was immersed in three paraffin baths in turn for 1 h each;

[0138] (5) Pour liquid paraffin into the mold box, then place the wax-soaked tissue block flat on the bottom, remove the embedding frame after the paraffin solidifies, and trim the wax block after it cools and hardens;

[0139] (6) Use a microtome to cut the paraffin-embedded tissue into slices of uniform thickness, approximately 4 mm.

[0140] (7) Dewax the paraffin sections in a gradient process of xylene for 10 min, xylene for 10 min, xylene for 10 min, anhydrous ethanol for 5 min, 90% ethanol for 5 min, 80% ethanol for 5 min, 70% ethanol for 5 min, and 50% ethanol for 5 min.

[0141] (8) Then, the paraffin sections were stained with hematoxylin for 0.5-1 min, rinsed with tap water, differentiated with 1% hydrochloric acid alcohol for a few seconds, rinsed with tap water, then blued with 1% ammonia aqueous solution for 1 min, rinsed with running water for a few seconds, stained with eosin stain for a few seconds, and rinsed with running water;

[0142] (9) Place the paraffin sections in 75% ethanol for 2 min, 85% ethanol for 2 min, anhydrous ethanol for 5 min, anhydrous ethanol for 5 min, and xylene for 5 min. Take the sections out of xylene and seal them with neutral gum.

[0143] The adhesion occurrence of ischemic nodule tissue and adhesion tissue was recorded and scored. The scoring criteria are shown in Table 3.

[0144] Table 3 Evaluation criteria for adhesion in peritoneal ischemia model

[0145]

[0146] Adhesion incidence = (ischemic nodules with adhesion / total number of ischemic nodules) * 100%

[0147] 4. Anti-adhesion effect

[0148] Use the Control group, The experimental results of the peritoneal ischemia model in the 4-group, 5-group, 7-group, 8-group, 10-group, 11-group, 12-group, 13-group, 14-group, 15-group, 16-group, 17-group, 18-group, 19-group, 20-group, 21-group, 22-group, 23-group, 24-group, 25 Figures 8 to 13 The results of adhesion rate, adhesion texture and adhesion toughness score of each group are shown in Fig.14 shown.

[0149] from Fig.14 The results showed that the adhesion incidence rates of PLA (2% NB) and PLA (4% NB) groups were 50±12.5% ​​and 21.88±11.97%, respectively, which were significantly lower than those of Control group (84.38±16.02%) and PLA group (90.63±11.92%). group (52.08±16.61%).

[0150] The anti-adhesion hydrogel group also had similar results. The adhesion rates of the SH (2 mg / mL) and SH (4 mg / mL) groups were 48.44±14.07% and 28.13±16.02%, respectively, which were significantly lower than those of the Control group (84.38±16.02%) and the SH group (75±17.6%). The adhesion incidence rate of the SH (4 mg / mL) group was lower than group (52.08±16.61%), and the difference was statistically significant.

[0151] In addition, the adhesion texture and adhesion toughness scores of PLA (4% NB) and SH (4 mg / mL) were significantly lower than those of Control and Group.

[0152] Control group, The results of HE staining of tissue samples obtained on the eighth day after the first surgery in the 4-group, 5-group, 7-group, 8-group, 9-group, 10-group, 11-group, 12-group, 13-group, 14-group, 15-group, 16-group, 17-group, 18-group, 19-group, 20-group, 21-group, 22-group, 23- Fig.15 As shown. Fig.15 The results of tissue section staining showed that the PLA (2% NB) group, PLA (4% NB) group, SH (2mg / mL) group and SH (4mg / mL) group were significantly higher than those of the Control group, The degree of inflammation in the peritoneal tissue of the group was significantly lower, and the number of fibroblasts was significantly reduced. This result shows that It can only function as a physical barrier, while the drug-loaded anti-adhesion membrane / anti-adhesion hydrogel of the present invention also has the effect of inhibiting inflammation and fibrosis.

[0153] The above results show that: using hexafluoroisopropanol as a solvent, under the voltage condition of 10-14kV, the electrospinning of nintedanib and anti-adhesion barrier, the prepared anti-adhesion film loaded with nintedanib has excellent anti-adhesion effect, which can significantly reduce the probability of adhesion and reduce the degree of adhesion, and the effect is significantly better than the currently commercially available Seprafilm anti-adhesion film (anti-adhesion hydrogel also has a similar effect). Therefore, the combination strategy of combining the anti-adhesion drug nintedanib with an absorbable barrier for the efficient prevention of postoperative adhesion is feasible and efficient.

[0154] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0155] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. An anti-adhesion film loaded with nintedanib, characterized in that: It is prepared by electrospinning a drug-loaded base material and nintedanib, wherein the drug-loaded base material is one or more of polylactic acid, polydioxanone, polylactic acid-glycolic acid copolymer, polycaprolactone, and polyethylene glycol; the solvent used in the electrospinning is hexafluoroisopropanol; and the voltage used in the electrospinning is 10 to 14 kV.

2. The anti-adhesion film loaded with nintedanib according to claim 1, characterized in that The voltage used in the electrostatic spinning is 11-13 kV.

3. The anti-adhesion film loaded with nintedanib according to claim 1, characterized in that The drug loading amount of the anti-adhesion membrane is 2wt% to 6wt%; preferably, the drug loading amount of the anti-adhesion membrane is 3.5wt% to 4.5wt%.

4. The anti-adhesion film loaded with nintedanib according to claim 1, characterized in that It is prepared from polylactic acid and nintedani cloth by electrostatic spinning; and / or, the loading amount of the anti-adhesion film is 3.5wt% to 4.5wt%.

5. The method for preparing the anti-adhesion film loaded with nintedanib according to any one of claims 1 to 4, characterized in that: The following steps are involved: The drug-loaded base material is dissolved in hexafluoroisopropanol, and then nintedanib is added and completely dissolved to obtain a spinning solution, which is subjected to electrospinning, dried to a constant weight, and sterilized by ultraviolet light.

6. The method for preparing the anti-adhesion film loaded with nintedanib according to claim 5, characterized in that, The voltage used in the electrospinning is 10-14 kV, preferably 11-13 kV; and / or, the electrospinning also includes the following parameters: outflow rate is 1.2±0.2 mL / min, drum speed is 200±20 rpm / min, slide speed is 30±3 mm / s, the distance between the needle and the drum is 15±1 cm, and the spinning temperature and humidity are 35±1°C and 40±2%.

7. An anti-adhesion hydrogel loaded with nintedanib, characterized in that: The anti-adhesion hydrogel is prepared from a drug-carrying base material and nintedanib, wherein the drug-carrying base material is one or more of carboxymethyl cellulose, oxidized regenerated cellulose, sodium hyaluronate and chitosan.

8. The anti-adhesion hydrogel loaded with nintedanib according to claim 7, characterized in that The concentration of nintedanib in the anti-adhesion hydrogel is 2 mg / mL to 6 mg / mL; preferably, the concentration of nintedanib in the anti-adhesion hydrogel is 3 mg / mL to 5 mg / mL; more preferably, the concentration of nintedanib in the anti-adhesion hydrogel is 3.5 mg / mL to 4.5 mg / mL.

9. The method for preparing the anti-adhesion hydrogel loaded with nintedanib according to claim 7 or 8, characterized in that: The following steps are involved: The drug-loaded base material is dissolved in deionized water, ultrasonicated for more than 4 hours, and then nintedanib is added. The drug-loaded base material is then extruded through sterile needles of 18G, 20G, 22G and 26G in sequence, 2 to 3 times each, and finally sterilized by a sterile filter membrane.

10. Use of the nintedanib-loaded anti-adhesion film according to any one of claims 1 to 4, or the nintedanib-loaded anti-adhesion hydrogel according to claim 7 or 8 in preventing postoperative adhesion.

Citation Information

Cited By

  • Nintedanib inhalation dry powder as well as preparation method and application thereof

    CN120837461A

  • Anti-adhesion membrane with coarse structure fibers and preparation method of anti-adhesion membrane

    CN121731562A

  • An anti-blocking film having a rough structure fiber and a method for manufacturing the same

    CN122805908A